Da zdravstvuyet SSSR-proobraz bratstva trudyashchikhsya vsekh natsional'nostey mira! - Lyushin, Vladimir (ОГИЗ - ИЗОГИЗ (Izogiz), 1933)
Emblem of the Soviet Union with workers of the world marching underneath with images of industry on the side Original title: Да здравствует СССР-прообраз братства трудящихся всех национальностей мира! PO-0125